T cell Co-Stimulatory molecules ICOS and CD28 stratify idiopathic pulmonary fibrosis survival. (2019) - Bonham, Catherine A.; Hrusch, Cara L.; Blaine, Kelly M.; Manns, Stephenie T.; Vij, Rekha; Oldham, Justin M.; Churpek, Matthew M.; Strek, Mary E.; Noth, Imre; Sperling, Anne I.
Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating disease that kills as many Americans as breast cancer each year. This study investigated whether lung function decline and survival associates with adaptive immunity in patients with IPF, specifically the expression of checkpoint molecules ICOS, CD28 and PD-1 on circulating CD4 T cells. Clinical data, blood samples and pulmonary function tests were collected prospectively and longitudinally from 59 patients with IPF over a study period of 5 years. Patients were followed until death, lung transplantation, or study end, and cell surface expression of CD45RO, CD28, ICOS, and PD-1 was measured on CD4 T cells via flow cytometry. Repeated measures of ICOS and CD28 on CD4 T cells revealed significant associations between declining ICOS and CD28 expression, and declining lung function parameters FVC and DLCO, independent of age, sex, race, smoking history, or immunosuppressant use. Strikingly, patients in the highest quintile of ICOS at study entry had markedly improved survival, while those with low CD28 fared poorly. No change in PD-1 expression was found. Analysis of ICOS and CD28 from the first blood draw identified three populations of IPF patients; those at high risk for early death, those with intermediate risk, and those at low risk. These results highlight the role of T cell mediated immunity in IPF survival, finding the assessment of two T cell stimulatory checkpoint molecules, CD28 and ICOS, was sufficient to discriminate three distinct survival trajectories over 5 years of patient follow up. Highlights: Decreased IPF lung function associates with declines in T cell checkpoint molecules ICOS and CD28. High ICOS associates with decreased mortality independently of gender, age, and pulmonary function. IPF patients with low T cell surface expression of CD28 had early mortality. A single measurement of ICOS and CD28 stratified IPF patients into 3 distinct survival trajectories.